Der Bauch des Fisches in byzantinischen Hymnen: Beispiele für die Rezeption von Jona 2:2–3 - OANCEA, Constantin-Horia (Studia Universitatis Babeș-Bolyai Sacra Scripta, 2026)
This study explores the influence of Jonah’s prayer (Jonah 2) on Byzantine hymns, emphasizing the interpretative perspective hymnographers use to understand the story of Jonah and the symbolism of the fish’s belly. After briefly describing how biblical scholarship approaches metaphor theory, three hymns are analyzed, focusing on their interpretation of Jonah 2,2–3. Byzantine hymnography makes extensive use of biblical imagery, which it develops in accordance with the liturgical year. The analysis shows that the understanding of this biblical episode largely depends on the liturgical year’s context. Hymnographers view the belly of the fish as a metaphor for sinful existence, an image of Christ’s tomb, or a figure for the Virgin Mary’s womb.